Structural performance evaluation of an aged structure using a modified plasticity model in inverse solution method. Issue 9 (2nd September 2018) - Labibzadeh, Mojtaba; Firouzi, Alireza; Ghafouri, Hamid R.
Abstract: In this research, the trends of degradation of stiffness and compressive strength of mass concrete of the Dez concrete arch dam, over time have been evaluated using a new and robust method. In previous studies of the corresponding author, he was successful to estimate the degradation of the stiffness of dam's concrete at the end of a selected time interval, i.e. the Year 2007 from the interval 1965–2007 using a novel thermal inverse analysis. But, he was interested in knowing the trend of this degradation over that time interval. In previous studies, the author used isotropic and transversely isotropic elastic material models for evaluating the stiffness degradation. By these material models, the reduction of the compressive strength of the mass concrete could not be determined. In this new attempt, to overcome the above-mentioned shortcomings, it was decided that the time interval is limited to a maximum of one year from 1965 to 2007. In addition, a more sophisticated material model for concrete of the dam, named as, concrete damaged plasticity model, from the ABAQUS standard material library, was employed to simulate the long-term concrete behaviour. By this material model, the reduction of the compressive strength of the dam's concrete could be measured. Obtained results demonstrated that the reduction of stiffness and strength of dam's concrete have not a constant rate of change and they have been accelerated considerably after passing approximately 20 years from the commissioning of the dam.